Renewable Energy Transitions as a Catalyst for Economic Growth and Job Creation in MENA - BACHIR, TLILI; Zineb, Himeur; Aicha, Gasmi; Louetri, Tarek; Bekkari, Soulaf (Journal of Ecohumanism, 2025)
This study examines the impact of renewable energy development on economic growth and employment creation across the four MENA regions during 2010–2024. Using annual time-series data and advanced econometric techniques, including the Vector Error Correction Model (VECM), the research investigates both long-term cointegration relationships and short-term dynamics among renewable energy production, GDP, employment, and foreign direct investment.The long-run analysis reveals a significant positive relationship between renewable energy production and economic growth, indicating that investments in renewable energy contribute to sustainable GDP expansion. Employment creation and foreign direct investment also exert positive effects, reinforcing the growth trajectory. In contrast, the short-run dynamics show that GDP primarily adjusts to deviations from long-term equilibrium, whereas renewable energy production and employment act as growth drivers with minimal short-term corrections, highlighting their weak exogeneity in the short run.These findings underscore the strategic importance of renewable energy policies and investments in promoting economic resilience, job creation, and sustainable development in MENA region. The study provides empirical evidence that enhancing renewable energy capacity can simultaneously foster economic growth and create employment opportunities, supporting policy recommendations for a transition toward a low-carbon, sustainable economy.